Kurikulum Jaringan Sekolah Islam Terpadu (JSIT) sebagai model integrasi kurikulum berbasis agama dan sains di SDIT Ulul Albab 2 Purworejo - Siti Khusniyati Sururiyah; Prawidya Lestari; Nur Rohmah Hayati (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
Achieving success in the world and the hereafter certainly requires processes and steps, in addition to worship as well as the provision of education, in particular requiring a curriculum. The current National Education System is deemed unable to answer the challenges and needs of society. That is why this is the reason for the emergence of Integrated Islamic Schools, including the Schools under the Integrated Islamic School Network (JSIT) which focus on combining religion and science, as part of society's response to their dissatisfaction with the existing National Education System. . This study aims to look at the application of the Integrated Islamic School Network (JSIT) curriculum as a model of curriculum integration based on religion and science at SDIT Ulul Albab 2 Purworejo, which seeks to respond by integrating and coordinating the curriculum. The research method used is a qualitative research method with a qualitative approach. The results of the study show that the integration of religion-based and science-based curricula implemented at SDIT Ulul Albab 2 Purworejo has 3 curricula, namely: the JSIT curriculum; Office and Ministry of Religion Curriculum; Al-Qur'an curriculum (tahfidz) which is applied simultaneously. The integration model of religion-based curriculum and science that is implemented in this school is generally more dominant on the basis of religion in all aspects. The application of science in this school is more about practical application in everyday life